Impact of Compaction Pressure and Heat Treatment Temperature on the Performance of FeSiBCuNb/FeNi Soft Magnetic Composites - Yanyan Song; Zhi Zhang; Shaoxiong Zhou; Ruibiao Zhang; Xiantao Li; Haichen Yu (Magnetochemistry)
FeSiBCuNb powders, produced via the gas–water atomization method, typically exhibit a broad particle size distribution and high sphericity. Nanocrystalline soft magnetic composites derived from these powders demonstrate exceptional service stability. In this study, a series of FeSiBCuNb/FeNi nanocrystalline magnetic powder cores (NMPCs) were fabricated under varying compaction pressures and heat treatment temperatures. The effects of these parameters on the soft magnetic properties were systematically analyzed. The findings reveal that optimizing compaction pressure and heat treatment temperature significantly enhances the density of the composite powders, leading to improved magnetic permeability and reduced core loss; when compaction pressure is 1800 MPa and heat treatment temperature is 550 °C, the NMPCs display outstanding magnetic properties with a low Hc of 6.32 Oe, high μe of 71.9, a low Pcv of 86.3 kW/m3 at 50 mT and 100 kHz, and 351.5 kW/m3 at 20 mT and 1000 kHz. Therefore, tailoring these processing conditions can enhance the soft magnetic performance of FeSiBCuNb nanocrystalline composites.